Puccini's Il trittico - Fisher, Burton D.; Adami, Giuseppe, 1878-1946; Adami, Giuseppe, 1878-1946; Forzano, Giovacchino; Forzano, Giovacchino; Forzano, Giovacchino; Forzano, Giovacchino; Puccini, Giacomo, 1858-1924 (Opera classics library., 2005)
A comprehensive guide to Puccini's IL TRITTICO (Il Tabarro, Suor Angelica, Gianni Schicchi), featuring insightful and in depth Commentary and Analysis of each opera, a complete, newly translated Libretto for each opera with Italian/English side-by side, and over 50 music highlight examples.